Management by task forces : a manual on the operation of interdisciplinary teams - Bass, Lawrence W. (Lawrence Wade), 1898- (Mt. Airy, Md. : Lomond Books, 1975)
Such task forces have proven of value in industries, public agencies, and developing countries. Composite task forces are a relatively recent managerial device for problemsolving by the coordinated exercise of diverse skills under the guidance of a team leader. In industry, task forces are being increasingly used for new product development. Most effective for this purpose is a group of specialists under a leader who coordinates their skills. Because of changing patterns of required expertise at successive stages, a sequence of interlocking teams is used to carry the concept forward through product and process definition, market estimation; product, process, and cost-benefit confirmation; and final approval for commercialization by top management. Task forces also are being adopted to plan corporate development and diversification by systematic comparison of the merits of alternatives. In such cases, they are valuable for feasibility studies, sales and production planning, plant location projects, and improvement of technical programs. Projects in the public sector can benefit from the inclusion of outside advisors and require techniques to obtain public consensus. National planning agencies in developing nations also can benefit by using task forces to increase the incisiveness of selection of industrial sectors for expansion and in formulating Government activities to stimulate growth. Examples of the organization and operation of task forces for these purposes are provided together with specific techniques and procedures. 12 tables, 5 charts, index, and 140 readings. (Author summary modified)
Includes index.
Bibliography: p. 183-192.
Keywords: Management committees